Percutaneous vertebroplasty and osteoplasty in pain relief treatment in bone metastases from kidney carcinoma - Brzozowski, Krzysztof; Żukowski, Paweł; Bogusławska, Romana; Szymański, Piotr; Korniluk, Jan (Contemporary Oncology/Współczesna Onkologia, 2007)
Metastases from the kidneys are usually placed into the lungs and/or into bone spongiosus structures (vertebral bodies and pelvis). Infiltration and destruction of bone structure is related to pain and is often a cause of fractures. In the case of vertebral body fracture we also have the possibility of neural radices compression and destabilization of the vertebral column. Percutaneous vertebroplasty and osteoplasty should allow the pain to be reduced or eliminated. These procedures are based on bone cement injection into metastases under fluoroscopy. The volume of cement is on average 2.5 ml. This treatment brings pain relief and is an effective procedure which stabilizes the vertebral body. These effects are induced by temperature and chemotoxicity during cement polymerization.